Strategic Insights into Establishing an English Course in Makassar: A SWOT Analysis of the 'My Liberty' Strategy - Ishafiuddin Ismail; Firman Firman (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the implementation of the "My Liberty" strategy for establishing an English course in Makassar, aiming to offer an innovative and holistic alternative to conventional language programs. Using a qualitative approach guided by grounded theory, the study employs SWOT analysis to assess the strategy’s strengths, weaknesses, opportunities, and threats. Data were collected through structured interviews with the course founders, who play central roles in both planning and execution. The interview protocol focused on strategic rationale, implementation steps, challenges faced, and potential for future development. Findings reveal that "My Liberty" distinguishes itself through a personalized curriculum, strong parental engagement, and enrichment activities that support holistic growth. Key strengths include its tailored content and trust-based parent relationships. However, initial challenges such as limited public exposure and operational inefficiencies emerged. Opportunities for growth include targeting elementary school students and leveraging online platforms to widen access. Persistent threats include low brand recognition and concerns regarding student well-being. The study highlights the potential of the "My Liberty" model to address gaps in traditional English education by combining innovation with community trust. At the same time, it underscores the need for improved outreach and operational refinement. This research offers practical insights for educators and entrepreneurs aiming to develop innovative language programs in urban settings. The findings provide strategic recommendations for refining educational initiatives in an increasingly competitive and dynamic environment.